2016
DOI: 10.1080/13607863.2015.1132675
|View full text |Cite
|
Sign up to set email alerts
|

Sensory loss and its consequences for couples’ psychosocial and relational wellbeing: an integrative review

Abstract: Although this review reports an association between sensory loss and couples' relational and psychosocial wellbeing, the results should be viewed with caution given that relatively few studies on couples' experiences of acquired sensory loss exist, and many have methodological limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…Hearing loss is a common chronic condition affecting older adults, and it is important for us to understand its impact on quality of life. 7 These findings highlight the need for improved methods of identifying individuals with age-related hearing loss and improving services for providing hearing aids, assistive listening devices, and auditory rehabilitation. Identifying individuals with hearing loss and supplying appropriate hearing aids or other listening devices and teaching coping strategies may have a positive impact on quality of life for older people.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss is a common chronic condition affecting older adults, and it is important for us to understand its impact on quality of life. 7 These findings highlight the need for improved methods of identifying individuals with age-related hearing loss and improving services for providing hearing aids, assistive listening devices, and auditory rehabilitation. Identifying individuals with hearing loss and supplying appropriate hearing aids or other listening devices and teaching coping strategies may have a positive impact on quality of life for older people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the psychosocial adjustment of adults with sensory loss (AWSLs) has suggested that social support, particularly from significant others such as a spouse, can buffer against social and emotional difficulties (Barron, Foxall, Von Dollen, Jones, & Shull, ; Bookwala, ). However, given that the primary negative consequences of sensory loss involve communication and social withdrawal, the ability to maintain mental well‐being and a supportive relationship when dealing with the loss of hearing and/or vision can be challenging for both AWSLs and their spouses (Lehane, Dammeyer, & Elsass, ).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of sensory loss is known to impact the well‐being of both partners in a relationship, yet most studies have reported only the results of one partner's experience, even when data on both partners have been collected (Lehane, Dammeyer, & Elsass, ). Thus, existing research examining couples’ functioning in the context of sensory loss has predominantly presented the intrapersonal perspective (Rusbult & Van Lange, ), that is, the effect of a participant's own perception and behaviour on their own well‐being (actor effects).…”
Section: Introductionmentioning
confidence: 99%
“…We did not examine gender differences in the present study due to uncertainty about the gender of the informant and the small sample size when restricted to spouses; however, post hoc analyses (unreported) did suggest that there were stronger associations between participant characteristics and informant distress when participants were men. Previous studies examining third-party impacts of sensory loss have typically been applied in the context of spousal [12,13,47] or care-recipient-giver relationships Fig. 1.…”
Section: Results From Ordinal Logistic Regression Showing Associationmentioning
confidence: 99%